Oncologic Nomogram for Stage I Rectal Cancer to Assist Patient Selection for Adjuvant (Chemo)Radiotherapy Following Local Excision - Zhao, Shutao; Chen, Xin; Wen, Dacheng; Zhang, Chao; Wang, Xudong (Frontiers in Oncology, 2021)
Background: Because of the low rate of lymph node metastasis in stage Ⅰ rectal cancer (RC), local resection (LR) can obtain high survival benefit and quality of life, but the indications for postoperative adjuvant therapy (AT) are still controversial. Methods: A retrospective analysis of 6,486 patients with RC (pT1/T2) after LR initially diagnosed from 2004 to 2016 was performed using the Surveillance, Epidemiology, and End Results (SEER) database, of which 5,519 were not receiving AT, 967 patients received AT. Propensity score matching (PSM) was used to balance the confounding factors of the two groups, and Kaplan-Meier method and Log-rank test were used for survival analysis. Cox proportional hazards regression analysis was used to screen independent prognostic factors and build a nomogram on this basis. X-tile software was used to divide the patients into low, moderate and high risk groups based on the nomogram risk score. Results: Multivariate analysis found that age, sex, race, marital status, size, T stage, and carcinoembryonic antigen (CEA) in the non-AT group were independent prognostic factors for stage I RC and were included in the nomogram prediction model. The C-index of the model was 0.726 (95% CI, 0.689-0.763). We divided the patients into three different risk groups according to the nomogram prediction score and found that the patients with low and moderate risk did not improve the prognosis after receiving AT, and the high risk patients benefited from AT. Conclusion: The nomogram of this study can effectively assess the prognosis of stage I RC patients undergoing LR. And high-risk patients we recommend AT after LR, low-risk patients do not recommend AT.